직장 내 괴롭힘이 정서적 고갈 및 조직몰입에 미치는 영향에 관한 연구 – 사회적 지원의 역할 - 정해숙(Hae Suk Jeong); 김현(Hyun Kim); 현병환(Byung HwanHyeon) (한국콘텐츠학회 논문지, 21(12), 2021)
This study examined significant differences in the impact of workplace bullying on emotional depletion and organizational commitment, and used 400 questionnaires to examine whether there would be significant differences depending on social support. As an analysis method, we used SPSS 24 for sample characteristics, SmartPLS 3 statistical programs for verifiable factor analysis, reliability and validity, path analysis, and structural equation models. Studies have shown that bullying in the workplace affects significant positive (+) for emotional depletion, and that emotional depletion affects significant negative (-) for tissue commitment. The influence relationship between workplace bullying and tissue commitment was partially mediated in the direction of wealth (-), and the effect of emotional depletion on tissue immersion was shown to be significant differences in the control of social support. Implications are that bullying in the workplace affects emotional depletion, so corporate efforts to prevent bullying are urgently needed, suggesting that employees can improve their organizational commitment, by using a system or community that can promote communication with their bosses. 본 연구는 직장 내 괴롭힘이 정서적 고갈 및 조직몰입에 미치는 영향에 유의한 차이를 살펴보고, 사회적 지원에 따른 유의한 차이가 있을 것인가를 고찰해 보고자 400부의 설문지를 활용하였다. 분석 방법으로 표본 특성에는 SPSS 24를 사용, 확인적 요인 분석, 신뢰도 및 타당도, 경로 분석, 구조방정식 모형에는 SmartPLS 3 통계 프로그램을 사용하였다. 연구 결과로는, 직장 내 괴롭힘은 정서적 고갈에 유의한 정(+)에 영향을 미치며, 정서적 고갈은 조직몰입에 유의한 부(-)의 영향을 미치는 것으로 나타났다. 직장 내 괴롭힘과 조직몰입 사이의 영향 관계에서 정서적 몰입은 부(-)의 방향으로 부분 매개하였고, 정서적 고갈이 조직몰입에 미치는 영향은 사회적 지원의 조절에 유의한 차이가 있는 것으로 나타났다. 시사점으로는 직장 내 괴롭힘은 정서적 고갈에 영향을 미치므로 괴롭힘을 예방하는 기업의 노력이 절실히 요구되며, 조직 내 상사와의 의사소통을 증진할 수 있는 제도나 커뮤니티를 활용하여 종사자들의 조직몰입을 향상할 수 있음을 시사해 주고 있다.